Pengaruh Terapi Murottal Al-Qur’an terhadap Tingkat Insomnia pada Lanjut Usia di Puskesmas Usuku Wakatobi - salam, syukriana; Alwi, Khidri; Ramli, Rahmawati (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Insomnia is a common health problem in the elderly. The aging process causes a decrease or change in physical and psychological conditions, thereby increasing sleep latency, decreasing sleep efficiency, and waking up earlier. This study aims to determine the effect of murottal Al-Qur'an therapy on reducing insomnia levels in the elderly. Murottal Al-Qur'an therapy is one of the healing methods that can reduce stress hormones and increase endorphins, thereby increasing feelings of relaxation and happiness. This study used a one-group pretest-posttest design. Data analysis used paired T test. The population in this study were elderly people who experienced insomnia of ​​Puskesmas Usuku Wakatobi with a sample of 30 people (15 people in the control group and 15 people in the intervention group). The control group was not given therapy while the intervention group was given therapy. Insomnia level measurements before (pretest) and after therapy (posttest) were carried out in both groups. The results of the study using the paired t test showed that the provision of Al-Qur'an murottal therapy can reduce the level of insomnia in the elderly by a significant level of 5%. Murottal Al-Qur'an therapy can reduce the number of insomnia sufferers to 5 people (33%) mild insomnia and 10 people (67%) recovered from insomnia. Whereas in the control group, there was no significant reduction in insomnia levels. It can be concluded that, giving murottal Al-Qur'an therapy with Surah Al-Rahman can reduce insomnia levels in the elderly in the working area of ​​Puskesmas Usuku Wakatobi.